1968
DOI: 10.1152/ajplegacy.1968.215.6.1442
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of physical factors affecting sodium reabsorption in the dog

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1969
1969
1984
1984

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…In view of our findings that proximal reabsorption is depressed by saline, it seems likely that this effect is exerted at a distal site. This would imply that capillary pressure may be an important physical determinant of distal reabsorption, as has been postulated for the proximal tubule (21,22).…”
Section: Methodsmentioning
confidence: 89%
“…In view of our findings that proximal reabsorption is depressed by saline, it seems likely that this effect is exerted at a distal site. This would imply that capillary pressure may be an important physical determinant of distal reabsorption, as has been postulated for the proximal tubule (21,22).…”
Section: Methodsmentioning
confidence: 89%
“…This has led to the suggestion that the postulated natriuretic hormone has a very short half-life, an observation not in keeping with our present experiments. An alternate explanation might be that since the recepient animals were not allowed to become volume expanded there was less depression of proximal tubular reabsorption due to physical change in the postglomerular circulation (13). Then less sodium would be delivered to the more distal site of action of the natriuretic hormone.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a hormone may be released which promotes renal sodium excretion (1, [8][9][10][11], perhaps by depressing proximal tubular sodium reabsorption (8,12). Recent studies also indicate that intrarenal physical changes in the postglomerular circulation (13)(14)(15) and possibly distributional changes in intrarenal blood flow (16)(17)(18) might be important in determining sodium excretion.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma volumes were determined in 10 BDL and 9 unoperated rats. After inulin and PAH clearances had been determined in the manner described earlier, carefully measured amounts (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) ACi) of radioiodinated ('I) human serum albumin (Abbott Laboratories, North Chicago, Ill.) were injected into the jugular vein. 60 min later, an arterial blood sample was drawn and the activity of 10 /Al of plasma was determined by liquid scintillation techniques, in an Iso/Cap 300 liquid scintillation system, with appropriate quenched standards and the scintillation solution described above.…”
Section: Methodsmentioning
confidence: 99%
“…Three phenomena thought to play a major role in altering the renal excretion of sodium are (a) changes in the glomerular filtration rate, (b) changes in the endogenous secretion of mineralocorticoids (3), and (c) renal hemodynamic adjustments, including disturbances in the intrarenal distribution of blood flow (5,6) and alterations of Starling forces within the peritubular circulation (12)(13)(14)(15). In the past, the possible interrelationship between the effects of these two hemodynamic adjustments has not been emphasized.…”
Section: Introductionmentioning
confidence: 99%